Mass and Q EC value of Si 26 - T. Eronen; V.-V. Elomaa; U. Hager; J. Hakala; A. Jokinen; A. Kankainen; T. Kessler; I. D. Moore; S. Rahaman; J. Rissanen; C. Weber; J. Äystö (Physical Review C, 2009)
BACKGROUND: Cytochrome P450 oxidoreductase deficiency (PORD) is a rare autosomal recessive disorder with heterogeneous endocrine, reproductive, DSD-related, and skeletal manifestations. Population-specific data in Chinese patients remain limited. METHODS: We described two Chinese probands with genetically confirmed PORD and systematically reviewed published Chinese cases. Clinical features, POR genotypes, skeletal manifestations, adrenal function, DSD phenotypes, and reproductive features were extracted. Carrier frequency and modeled genetic prevalence were estimated using gnomAD and WBBC, with variants stratified according to evidence for pathogenicity. RESULTS: The pooled cohort included 40 unique Chinese patients, comprising two newly reported probands and 38 literature-derived cases. One proband carried p.R457H and a novel frameshift variant, p.N178Efs*28; the second carried p.R457H and p.Y607C. The recurrent p.R457H variant accounted for 40 of 80 alleles in the Chinese cohort. Using the expanded exploratory variant set, the modeled genetic prevalence was 2.4 per 1,000,000 individuals in WBBC Chinese and 3.3 per 1,000,000 individuals in gnomAD East Asians. CONCLUSIONS: Chinese patients with PORD show broad clinical heterogeneity, and p.R457H is a recurrent East Asian-enriched POR variant. The novel p.N178Efs*28 variant expands the POR mutational spectrum. Population-database estimates should be interpreted as modeled genetic prevalence rather than observed clinical incidence, especially when predicted deleterious variants are included.